Generating Novel Male Sterile Tomatoes by Editing Respiratory Burst Oxidase Homolog Genes - Dai, Xiaojuan; Han, Huanan; Huang, Wei; Zhao, Lianghui; Song, Minglei; Cao, Xuesong; Liu, Chenglan; Niu, Xiaomu; Lang, Zhaobo; Ma, Changle; Xie, Hongtao (Frontiers in Plant Science, 2022)
Cross breeding of tomatoes (Solanum lycopersicum), an important vegetable crop, is an effective way to improve yield and enhance disease and stress resistance. However, the efficiency of tomato hybridization is hindered by self-fertilization, which can be overcome using male sterile lines. It has been reported that reactive oxygen species (ROS) act as a key regulator for anther development, mediated by RBOH (Respiratory Burst Oxidase Homologue) genes. Here, two tomato anther-expressed genes, LeRBOH (Solyc01g099620) and LeRBOHE (Solyc07g042460), were selected to cultivate novel tomato male sterile strains. By using a CRISPR/Cas9 system with a two-sgRNA module, the lerboh, lerbohe, and lerboh lerbohe mutant lines were generated, among which the lerbohe and lerboh lerbohe mutants displayed complete male sterility but could accept wild-type pollens and produce fruits normally. Further analysis uncovered significantly decreased ROS levels and abnormal programmed cell death in lerboh lerbohe anthers, indicating a key role of ROS metabolism in tomato pollen development. Taken together, our work demonstrates a successful application of gene editing via CRISPR/Cas9 in generating male sterile tomatoes and afforded helpful information for understanding how RBOH genes regulating tomato reproduction process.